Exploring the Physical Activity Counselling for Patients With Rheumatoid Arthritis—Perceptions of Nurses and Physiotherapists - Lehtomäki, Katja; Ryhtä, Iina; Peltonen, Jaana; Stolt, Minna (Wiley, 2025)
Background: Physical activity is beneficial for patients with rheumatoid arthritis (RA). However, little is known about how healthcare professionals counsel and support patients with RA to be physically active. Aim: This study aims to explore nurses' and physiotherapists' perceptions of delivering physical activity counselling for patients with RA during routine follow-up appointments. Method: A mixed-methods convergent parallel design was employed, using survey and interview data from nurses and physiotherapists (n = 9) at a rheumatology outpatient clinic. Statistical and inductive content analyses were conducted. COREQ guidelines were followed. Findings: Nurses and physiotherapists perceived physical activity counselling to be central in the overall RA care. They considered it partly challenging as delivering effective counselling requires understanding the specific characteristics of RA and tailoring advice to the individual patient's needs. In general, they focused on motivating patients to be physically active by demonstrating the benefits of physical activity. However, they also reported a lack of awareness regarding the content discussed during each other's appointments, highlighting issues with information sharing between professionals. Conclusion: Physical activity counselling is multidimensional, constitutes part of professional competence and requires extensive knowledge of RA and physical activity recommendations. Future interventions are needed to enhance nurses' and physiotherapists' competence in delivering physical activity counselling.